Restrepia santanderensis (Orchidaceae: Pleurothallidinae), a new species from the western slope of the eastern Andes in Colombia - Gutiérrez Morales, Nicolás; Moreno, Juan Sebastián; Karremans, Adam P.; Gil-Amaya, Karen (Phytotaxa, 2023)
A new species of the orchid genus Restrepia from the department of Santander, in the western slope of the eastern Andes of Colombia, is described and illustrated. Restrepia santanderensis is compared with the morphologically similar R. flosculata and R. mendozae, which share having short inflorescences and small to medium yellow flowers. The new species can be recognized by its ramicauls prominently covered by brown-dotted sheaths, with the uppermost sheath elongate as long as the peduncle, the sepals partially spreading, the synsepal with glandular trichomes along the veins of the adaxial surface, the straight petals and the rectangular lip with truncate apex. Comparisons with similar species and comments on its ecology are provided.